REB reflection from the boundary plasma-vacuum - Egorov, A.M.; Lapshin, V.I.; Maslov, V.I.; Onishchenko, I.N.; Skorobagatko, G.A. (Вопросы атомной науки и техники, 2004)
The necessary conditions of the experimentally observed reflection of "tail" of the dense relativistic electron
beam from the plasma-vacuum boundary at once after full its injection into the plasma under condition of nb.>>n0,
are considered in this paper. У статті розглядаються необхідні умови відбиття, що експериментально спостерігається, «хвоста»
інжектованого щільного nb.>>n0 релятивістського електронного згустку від границі плазма-вакуум після
повного його проникнення в плазму. В статье рассматриваются необходимые условия экспериментально наблюдаемого отражения «хвоста»
инжектируемого плотного nb.>>n0 релятивистского электронного сгустка от границы плазма-вакуум после
полного его проникновения в плазму.